Foundations of evidence-based social work practice - Roberts, Albert R.; Yeager, Kenneth (Oxford ; New York : Oxford University Press, 2006)
"Concise introduction to evidence-based social work that introduces the issues and methods most frequently encountered while preparing for evidence-based social work practice"--Provided by publisher.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Evidence-based social work; Human services -- Research -- Methodology; Psychiatric social work; Electronic books